Degradation of Standard Dyes and Textile Wastewater as a Pollutant Model Using Gamma Radiation - A. Sumartono (Atom Indonesia, 2008)
A degradation and a decoloration of textile wastewater using ionizing radiation are already applied which some factors influence i.e. original wastewater, pH, pollutant concentration, solubility and variation of polutant. A dyes standard had been treated using ionizing radiation and the mechanism degradation will be discussed. The percentage of the dye degradation about 90-99% at doses of 2-10 kGy. The degradation of textile wastewater using gamma radiation is was carried out at doses of 25 kGy. The combination of irradiation and the addition of coagulant caused the decoloration and the degradation of the textile wastewater.